Wojewódzka Rada Związków Zawodowych w Zielonej Górze w latach 1950-1956 - Chojak, Jarosław (In Gremium. Studies in History, Culture and Politics, 2015)
The Provincial Council of Trade Unions in Zielona Góra , 1950-1956 The Provincial Council of Trade Unions in Zielona Góra was founded in 1950 as a result of adapting the structures of the unions to the new administrative division of the country. Its range coincided with the newly created province of Zielona Gora. The first Provincial Conference of Trade Unions was held on 17 September 1950. The first chairman was Bogdan Swiderski. The territorial structures were formed immediately, but the branch organizations and other organizational units only partially transferred their regional authorities to Zielona Gora. Others had their offices in Wroclaw and Poznan. The situation was difficult also because of continuous reorganization of industries. This led to a conflict of jurisdiction. One can find many critical voices at the federal authorities in the reports of the meetings of trade union organizations, especially the fact of neglecting employee issues, the pursuit of plans and production commitments. The competition, a constant struggle for higher production output became the primary objective of trade unions. Clerks, teachers and students were involved as well.